ChemInform Abstract: CrVI→CrV Transition in Uranyl Chromium Compounds: Synthesis and High‐Temperature X‐Ray Diffraction Study of Cs2[(UO2)2(CrO4)3]. Issue 2 (14th January 2014) - Siidra, Oleg I.; Nazarchuk, Evgeny V.; Kayukov, Roman A.; Bubnova, Rimma S.; Krivovichev, Sergey V.
Abstract Single crystals of Cs2[(UO2)2(CrO4)3] are hydrothermally synthesized from aqueous mixtures of (UO2)(NO3)2, CsNO3, and CrO3 (autoclave, 100 °C, 7 d, 92% yield).